Reliability analysis for two-unit system composing of an intermittent operation unit - Dinh Duc Hanh; Quang Bang Tao; Pham Nguyen Quoc Huy; Nguyen Linh Giang (Tạp chí Khoa học và Công nghệ, 2023)
In this paper, a close-form reliability analysis for two-unit system consisting of an intermittent operation (IO) component and a continuous operation (CO) component is developed. While the CO component continuously works, the IO component alternatively works in both operation and standby modes. The deterioration of the CO component could lead to increase working frequency of the IO component, which in result, could speed up the deterioration process of the IO component. Ignoring this deterioration interaction in deterioration modeling and reliability analysis could lead to inaccuracy in lifetime prediction and maintenance planning. Therefore, a deterioration model for the IO component is developed taking into account the deterioration between components. Reliability model of the IO component and the whole system are then derived.